Thyroid carcinoma - Botta, Fernando (Cirugía del Uruguay, 1992)
Reference is made to the diagnostica! evaluation of thyroid nodu/es. reaffirming concepts of study algorythm. sensitivity and specificity of diagnostica/ procedures and cost-effectiveness. The author emphasizes the importance of cytology. patient selection for surgery. surgical tactics, and the need of multidisciplinary protocolization in the study and treatment of this pathology. The most controversia/ issues concerning treatment of differentiated carcinoma of the thyroid, the sine qua non condition of pathologist presence in the operating room in thyroid surgery and the value of nuclear DNA quantification in the dignosis and prognosis of these tumors are briefly mentioned.